Pengembangan Media Pembelajaran Interaktif Canva Materi Jaringan Komputer Kelas 11 MA Al Fattahiyyah - Ammana Baiti Muslimah; Fahrur Rozi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Canva-based interactive learning media is a tool designed to create engaging and interactive learning materials using the Canva graphic design platform. This study aims to develop and determine the appropriateness of this media for the Informatics subject, Computer Networks and the Internet, for 11th-grade students of Social Sciences 1 at MA Al-Fattahiyyah. The method used was Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The material was adapted to the 11th-grade teaching modules at MA Al-Fattahiyyah. This study involved two lecturers, one media expert, and students as respondents. The research instruments included a media appropriateness assessment sheet, a material assessment sheet, and a student response questionnaire. The assessment results showed the media received a score of 95% from Media Expert 1, 77.5% from Media Expert 2, 89.28% from the material expert, 82% from the small group trial, and 91.48% from the large group trial. These results concluded that the media was deemed